2001
DOI: 10.1002/cne.1383
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the heart and aorta of Manduca sexta

Abstract: Innervation of the heart and aorta of Manduca sexta was studied by using anatomic, neuronal tracing and immunocytochemical techniques. The study was undertaken to provide a foundation for investigating the neural mechanisms controlling cardiac reversal in adults. Lateral cardiac nerves were not found in the larval or adult heart. The larval heart and aorta seem to lack innervation, but a neurohemal system for the release of a cardioactive peptide is associated with the larval alary muscles. At adult metamorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 57 publications
(85 reference statements)
5
25
0
1
Order By: Relevance
“…We have previously shown that in newly eclosed mosquitoes, CCAP is highly expressed in neurons 27 and IN704 of the ventral nerve cord, but that these neurons undergo apoptosis by 12h post-eclosion (Honegger et al, 2011). This is similar to what has been reported for Manduca sexta immatures (Ewer et al, 1998;Davis et al, 2001). In the present study we show that in newly eclosed mosquitoes, neurons 27 extend numerous peripheral projections that span the pleuron and innervate the alary and cardiac muscles, as is also seen in M. sexta and Baculum extradendatum Ejaz and Lange, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…We have previously shown that in newly eclosed mosquitoes, CCAP is highly expressed in neurons 27 and IN704 of the ventral nerve cord, but that these neurons undergo apoptosis by 12h post-eclosion (Honegger et al, 2011). This is similar to what has been reported for Manduca sexta immatures (Ewer et al, 1998;Davis et al, 2001). In the present study we show that in newly eclosed mosquitoes, neurons 27 extend numerous peripheral projections that span the pleuron and innervate the alary and cardiac muscles, as is also seen in M. sexta and Baculum extradendatum Ejaz and Lange, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…8F). At all the stages examined, the observed pattern and density of FM1-43 staining on the foregut was similar to that observed following synaptotagmin immunocytochemistry (Davis et al, 2001;Littleton et al, 1993; Fig. 8G,H).…”
Section: Fm1-43 Staining Reveals a Deficit In Presynaptic Activity Ofsupporting
confidence: 82%
“…Klukas et al confirmed that these SEG neurons were CCAP-IR (Klukas et al, 1996), which was also consistent with neurons identified in the CCAP gene expression study (Loi et al, 2001). Lastly, Davis et al provided evidence for neurohemal release sites from the SEG of CCAP in the vicinity of the aorta and anterior foregut (Davis et al, 2001). Our finding of CCAP-IR neurohemal-like structures on the muscles of the anterior foregut (Fig.·4) is consistent with these previous studies.…”
Section: A Blood-borne Factor Acts To Suppress Anterior Foregut Motilitysupporting
confidence: 92%
“…Using CCAP antiserum, we labeled possible release sites on the muscles of the anterior foregut (shown in Fig.·4, the anterior foregut esophageal dilators). This labeling was reminiscent of CCAP-ir neurohemal structures found on other M. sexta tissues and in other species (Davis et al, 2001;Donini et al, 2002). With these data in mind, we wanted to test whether CCAP also plays a role in triggering the return of the peristaltic contractions of the anterior foregut observed at the end of the molt.…”
Section: P<0001)mentioning
confidence: 86%
See 1 more Smart Citation